Multifunctional liquid metal-based nanoparticles with glycolysis and mitochondrial metabolism inhibition for tumor photothermal therapy. (February 2022) - Ding, Xing-Lan; Liu, Miao-Deng; Cheng, Qian; Guo, Wen-Hui; Niu, Mei-Ting; Huang, Qian-Xiao; Zeng, Xuan; Zhang, Xian-Zheng
Abstract: Tumor cells obtain energy supply from different metabolic pathways to maintain survival. In this study, a tumor acidity-responsive spherical nanoparticle (called as LMGC) was designed by attaching glucose oxidase (GOx) and mineralizing calcium carbonate on the surface of liquid metal nanoparticles to integrate the synergistic effect of adenosine triphosphate (ATP) generation inhibition and photothermal therapy (PTT) for enhanced tumor therapy. After GOx catalysis, the process of glycolysis was inhibited, and the increased H2 O2 level enhanced the intratumoral oxidative stress. Besides, the gluconic acid production accelerated the degradation of LMGC and promoted Ca 2+ -mediated mitochondrial dysfunction. The inhibition of glycolysis and mitochondrial metabolism could significantly reduce ATP production and down-regulate heat shock protein (HSP) expression, which would reduce tumor cells heat resistance and improve PTT therapeutic effect. This liquid metal-based ATP inhibition system with enhanced therapeutic effect will find great potential for tumor treatment.